CASE REPORTSCo-existence of a rare dyspnea with pericardial diaphragmatic rupture and pericardial rupture: a case report - Öz, Necdet; Kargı, Ahmet Bülent; Zeybek, Arife (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Pericardial-diaphragmatic rupture is a rare condition which occurs after blunt trauma and involves the herniation of abdominal organs into the pericardium. A 77-year-old female patient presenting with complaints of palpitation and difficulty in breathing was admitted to the emergency room. Left lateral thoracotomy revealed the herniation of abdominal organs into the thorax. A pericardial-diaphragmatic rupture and a pericardial rupture were found to co-exist. The diaphragm and the pericardium were repaired primarily. The case is presented here because herniation of abdominal organs into the pleural cavity through the pericardium is a rare condition.